let A, B, C, D, E, F, J be set ; :: thesis: for h being Function
for A9, B9, C9, D9, E9, F9, J9 being set st A <> B & A <> C & A <> D & A <> E & A <> F & A <> J & B <> C & B <> D & B <> E & B <> F & B <> J & C <> D & C <> E & C <> F & C <> J & D <> E & D <> F & D <> J & E <> F & E <> J & F <> J & h = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) +* (A .--> A9) holds
( h . A = A9 & h . B = B9 & h . C = C9 & h . D = D9 & h . E = E9 & h . F = F9 & h . J = J9 )

let h be Function; :: thesis: for A9, B9, C9, D9, E9, F9, J9 being set st A <> B & A <> C & A <> D & A <> E & A <> F & A <> J & B <> C & B <> D & B <> E & B <> F & B <> J & C <> D & C <> E & C <> F & C <> J & D <> E & D <> F & D <> J & E <> F & E <> J & F <> J & h = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) +* (A .--> A9) holds
( h . A = A9 & h . B = B9 & h . C = C9 & h . D = D9 & h . E = E9 & h . F = F9 & h . J = J9 )

let A9, B9, C9, D9, E9, F9, J9 be set ; :: thesis: ( A <> B & A <> C & A <> D & A <> E & A <> F & A <> J & B <> C & B <> D & B <> E & B <> F & B <> J & C <> D & C <> E & C <> F & C <> J & D <> E & D <> F & D <> J & E <> F & E <> J & F <> J & h = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) +* (A .--> A9) implies ( h . A = A9 & h . B = B9 & h . C = C9 & h . D = D9 & h . E = E9 & h . F = F9 & h . J = J9 ) )
assume that
A1: A <> B and
A2: A <> C and
A3: A <> D and
A4: A <> E and
A5: A <> F and
A6: A <> J and
A7: ( B <> C & B <> D & B <> E & B <> F & B <> J & C <> D & C <> E & C <> F & C <> J & D <> E & D <> F & D <> J & E <> F & E <> J & F <> J ) and
A8: h = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) +* (A .--> A9) ; :: thesis: ( h . A = A9 & h . B = B9 & h . C = C9 & h . D = D9 & h . E = E9 & h . F = F9 & h . J = J9 )
A in dom (A .--> A9) by TARSKI:def 1;
then A10: h . A = (A .--> A9) . A by ;
not J in dom (A .--> A9) by ;
then A11: h . J = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) . J by
.= J9 by ;
not F in dom (A .--> A9) by ;
then A12: h . F = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) . F by
.= F9 by ;
not E in dom (A .--> A9) by ;
then A13: h . E = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) . E by
.= E9 by ;
not D in dom (A .--> A9) by ;
then A14: h . D = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) . D by
.= D9 by ;
not C in dom (A .--> A9) by ;
then A15: h . C = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) . C by
.= C9 by ;
not B in dom (A .--> A9) by ;
then h . B = ((((((B .--> B9) +* (C .--> C9)) +* (D .--> D9)) +* (E .--> E9)) +* (F .--> F9)) +* (J .--> J9)) . B by
.= B9 by ;
hence ( h . A = A9 & h . B = B9 & h . C = C9 & h . D = D9 & h . E = E9 & h . F = F9 & h . J = J9 ) by ; :: thesis: verum